Analisis Penerimaan Google Classroom Bagi Mahasiswa UPN "Veteran" Jawa Timur Menggunakan Model UTAUT - Khurrotul 'Uyun; Najwa Fathiro Cahyono; Faradila Kusuma Dewi (KOLONI, 2023)
Google Classroom is a learning platform designed to assist teachers in addressing difficulties in creating, sharing, and organizing assignments using digital media. This research aims to determine the acceptance of UPN "Veteran" Jawa Timur students towards the Google Classroom application using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The UTAUT model is used as a framework in this research to identify factors influencing students' acceptance of Google Classroom usage. The research method employed a descriptive quantitative approach with purposive sampling technique. The sample consisted of 100 respondents, and a questionnaire was used for data collection. The results of this research are expected to enhance our understanding of the factors influencing the acceptance of Google Classroom by UPN "Veteran" Jawa Timur students. In the future, these research findings can serve as a basis for improving and developing Google Classroom as a more efficient learning platform. The research demonstrates strong significance in the influence of Social Influence on Behavioral Intention and Behavioral Intention on Use Behavior. However, a weak influence is indicated by the relationship between Effort Expectancy and Behavioral Intention.  Keywords: Google Classroom, UTAUT, Technology Acceptance, Students